CATHODIC ELECTRODEPOSITION OF Cu 4 SnS 4 THIN FILMS FROM ACIDIC SOLUTION - Anuar Kassim; Ho Soon Min; Zulkefly Kuang; Tan Wee Tee; Abdul Halim Abdullah; Atan Sharif; Md. Jelas Haron; Saravanan Nagalingam (ASEAN Journal on Science and Technology for Development, 2009)
In this work the synthesis of copper tin sulfide thin films by electrodeposition is carried out. The films were deposited onto ITO glass substrates from an aqueous solution bath containing copper sulfate, tin chloride and sodium thiosulfate at pH 1 and room temperature. Prior to the deposition, a cyclic voltammetry experiment was carried out  between two potential limits (+1000 to -1000 mV versus Ag/AgCl) to probe the effect of  the applied potential and to determine the most likely suitable electrodeposition potential  for the deposition of copper tin sulfide. The deposition was attempted at various cathodic potentials such as -400, -600, -800, -1000 mV to determine the optimum deposition  potential. The films have been characterized by techniques such as optical absorption, Xray diffraction  and  atomic  force  microscopy. The XRD patterns show that the films are polycrystalline with orthorhombic structure. The AFM studies reveal the electrodeposited films were smooth, compact and uniform at deposition potentials of –600 mV versus  Ag/AgCl. The direct optical band-gap energy was obtained to be 1.58 eV.